ANALISIS FAKTOR KESULITAN BELAJAR MATEMATIKA SISWA SMP DALAM MENGOPTIMALKAN PEMBELAJARAN SECARA DARING - Norhaliza Norhaliza; Selfiana Purnama Sari; Iin Ariyanti (Universitas Muhammadiyah Metro, 2022)
This study aims to find out what are the factors that cause junior high school students to have difficulty in learning mathematics online. This type of research is a quantitative research, the method used in this research is descriptive by using a student response questionnaire instrument in the form of a Google Form which contains 12 statements derived from several indicators. The subjects in this study were students of class VIII SMP Negeri 2 Mandastana, totaling 31 students. The results of this study indicate that students' difficulties with online learning are relatively low with a percentage level of 41%, there is only one indicator that shows students' difficulties in online learning, namely the attitude indicator with a percentage of 60%. So it can be concluded that students are pretty good at online learning even though it is seen from the google form data that there are still obstacles that students experience in carrying out online mathematics learning but it does not give more influence.